An assessment of potential unintended consequences following a national antimicrobial stewardship programme in England: an interrupted time series analysis - Balinskaite,V; Bou-Antoun,S; Johnson,AP; Holmes,A; Aylin,P (Clinical Infectious Diseases, 2019)
Background: The 'Quality Premium' (QP) introduced in England in 2015 aimed to financially reward local healthcare commissioners for targeted reductions in primary care antibiotic prescribing. We aimed to evaluate possible unintended clinical outcomes related to this QP. Methods: Using Clinical Practice Research Datalink and Hospital Episode Statistics datasets, we examined general practitioner (GP) consultations (visits) and emergency hospital admissions related to a series of pre-defined conditions of unintended consequences of reduced prescribing. Monthly age and sex-standardised rates were calculated using a direct method of standardisation. We used segmented regression analysis of interrupted time series to evaluate the impact of the QP on seasonally adjusted outcome rates. Results: We identified 27,334 GP consultations and over five million emergency hospital admissions with pre-defined conditions. There was no evidence that the QP was associated with changes in GP consultation and hospital admission rates for the selected conditions combined. However, when each condition was considered separately, a significant increase in hospital admission rates was noted for quinsy, and significant decreases were seen for hospital-acquired pneumonia, scarlet fever, pyelonephritis and complicated urinary tract conditions. A significant decrease in GP consultation rates was estimated for empyema and scarlet fever. No significant changes were observed for other conditions. Conclusions: Findings from this study show that overall there was no significant association between the intervention and unintended clinical consequences, with the exception of a few specific conditions, most of which could be explained through other parallel policy changes or should be interpreted with caution due to small numbers.